Systematic study on key factors influencing establish automobile electronics industry clustering: From talent program perspective - Nai-Chieh Wei; Hsiang-Chen Hsu; I-Ming Chao; Ai-Ling Yang (Journal of Industry-University Collaboration (JIUC), 2019)
Purpose The purpose of this paper is to analyze the trends of global automobile industry toward energy saving and smart application. The automobile industry has its own special supply, safety and reliability system. It combined with the legislations that progressive safety driving leads to increase automobile electronic (AE) facilities and enlarges the proportion of the electronic control for vehicles. Based on matured communication and semiconductor industries in Taiwan, the government assists these hi-tech industries in entering the AE domain by clustering relevant enterprises with assembly supply chains. Flagship IC packaging and LCD panels enterprises are located in the Kaohsiung Industrial Park which possesses advantages for the clustering of AE industry. Design/methodology/approach In this paper, a systematic investigation on establishing AE industry cluster in Kaohsiung Industry Park (KIP) is presented. First, 42 electrical and electronics enterprises are site visited and interviewed for operation and management preferential demands. Second, problems encountered in enterprises' operation are identified through expert weight method. Third, the main factors involved in the operational management are then analyzed based on five flagship enterprises in KIP. The integration of industrial-university-government resources and assistance is demonstrated. Finally, the establishment of an innovative talents cultivation model is illustrated. Findings The developed systematic talent program is proposed to resolve the urgent demands in recruiting talents, operational costs and new products development. Originality/value This paper satisfies needs of research enterprise management. The establishment of an innovative talents cultivation model is illustrated.
Keywords: 330; Automobile electronics; Experts weighting method; Industry cluster; Kaohsiung Industry Park; Systematic talent programme